Top management team career experience heterogeneity, digital transformation, and the corporate green innovation: a moderated mediation analysis - Gao, Daquan; Li, Songsong; Guo, Chang (Frontiers in Psychology, 2023)
Introduction Drawing upon upper echelon theory and the resource-based view, this study employs a moderated mediation model to investigate the moderating role and underlying mechanisms of digital transformation in the influence of top management teams (TMT) on corporate green innovation. Methods Our analysis of panel data from 19,155 Chinese A-share listed companies (2011–2020) demonstrates that TMT career experience heterogeneity has a positive effect on green innovation, a relationship that is further strengthened by digital transformation. Results This study shows the role of digital transformation in amplifying the effects of TMT diversity on green innovation and the crucial role of industry-academia-research collaboration as a mediator. Heterogeneity analysis highlights that non-state-owned enterprises (non-SOEs) show more agility than state-owned enterprises (SOEs) in leveraging heterogeneous TMT to drive green innovation. Conversely, green innovation in SOEs benefits more from digital transformation, which includes both its direct and indirect effects of digital transformation. Enterprises located in non-Yangtze River Economic Belt regions benefit more from digital transformation, demonstrating the importance of a balanced distribution of digital resources. Discussion This study provides novel insights into leveraging inclusive leadership and digital capabilities to enhance ecological sustainability. This study underscores the potential of diversified TMTs and digitalization technology integration to catalyze green innovation, which is critical for environmentally responsible transformation.